2019
DOI: 10.1007/s00586-019-06099-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of Enneking appropriate versus Enneking inappropriate procedure in patients with primary osteosarcoma of the spine: a systematic review with meta-analysis

Abstract: Purpose:Primary osteosarcoma of the spine is a rare osseous tumour. En bloc resection, in contrast with intralesional resection, is the only procedure able to provide Enneking appropriate (EA) margins, which has improved local control and survival of patients with primary osteosarcoma of the spine. The objective of this study is to compare the risk of local recurrence, metastases development and survival in patients with primary osteosarcoma of the spine submitted to Enneking appropriate (EA) and Enneking inap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…Der Resektionsrand kann daher als Enneking appropriate (EA)eine marginale oder eine weite Resektion oder als Enneking inappropriate (EI)eine intraläsionale oder eine kontaminierte Resektion bezeichnet werden [19]. Eine EA Resektion führt zur einen deutlichen Reduktion der Rezidivrate und Metastasierung sowie zur Verlängerung des Gesamtüberlebens [20,21].…”
Section: Operative Behandlungunclassified
“…Der Resektionsrand kann daher als Enneking appropriate (EA)eine marginale oder eine weite Resektion oder als Enneking inappropriate (EI)eine intraläsionale oder eine kontaminierte Resektion bezeichnet werden [19]. Eine EA Resektion führt zur einen deutlichen Reduktion der Rezidivrate und Metastasierung sowie zur Verlängerung des Gesamtüberlebens [20,21].…”
Section: Operative Behandlungunclassified
“…Spinal OS is rare accounting for less than 5% of malignant tumours of the spine [168]. They are aggressive with an overall median survival of 6.7 years [169].…”
Section: Relevance To Spinal Surgerymentioning
confidence: 99%
“…Surgical excisions are termed Enneking appropriate (for en-bloc resection with marginal margin) or Enneking inappropriate (positive margin at histology). Reduced local recurrence and longer disease-free survival is achieved with Enneking appropriate resections [168,169].…”
Section: Relevance To Spinal Surgerymentioning
confidence: 99%
“… 1 Recent studies suggested that primary malignant spinal tumors including osteosarcoma should undergo en bloc resection to reduce local recurrence and achieve a complete cure with longer survival. 1 - 5 Although total en bloc spondylectomy (TES) 6 , 7 can achieve marginal resection of tumors, this procedure requires sacrifice of nerve root and carries major risks, including massive bleeding, spinal cord injury, pleural effusion, and postoperative cerebrospinal fluid leakage. 3 , 8 However, complete marginal resection is not always achievable due to adjacent neurovascular components and impending neurological dysfunction sometimes makes it impossible to perform neoadjuvant therapies aiming for maximizing the chance of marginal resection.…”
Section: Introductionmentioning
confidence: 99%